2022
DOI: 10.17275/per.22.10.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking Skills of Environmental Changes: A Biological Instruction Using Guided Discovery Learning-Argument Mapping (GDL-AM)

Abstract: Based on the development of education in Indonesia today, teachers still teach in ways that make students memorize lessons. A learning model is needed that can support students to think critically. One of the learning models that can support students to think critically is through guided discovery learning model with argument mapping. This study aims to find out the influence of guided discovery learning models with an argument mapping to develop critical thinking skills. The research method used was quasi exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
1
10
1
Order By: Relevance
“…Based on the results of the study, it was stated that there was a positive relationship between personality and pro-environmental behavior in students of SMAN 27 Jakarta. Likewise research was found that there was an effect of guided discovery learning with argument mapping on the critical thinking skills of high school students (Nurhayati, Nurjamil, et al, 2022;Ristanto et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on the results of the study, it was stated that there was a positive relationship between personality and pro-environmental behavior in students of SMAN 27 Jakarta. Likewise research was found that there was an effect of guided discovery learning with argument mapping on the critical thinking skills of high school students (Nurhayati, Nurjamil, et al, 2022;Ristanto et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…Likewise research that stated that there was a positive relationship between personality and pro-environmental behavior in students. From this study, it was concluded that there was an effect of guided discovery learning with argument mapping on the critical thinking skills of high school students (Datau et al, 2019;Ristanto et al, 2022). Then previous research aims to determine students' initial critical thinking skills (Nurhayati, Agustini, et al, 2022).…”
Section: Introductionmentioning
confidence: 93%
“…According to Kuloğlu (2022) pertaining to 21st-century skills, (Fletcher & Dumford, 2021) teachers have a responsibility to guide and encourage production readiness, curiosity, problem-solving skills, and critical thinking in their students. Thorndahl & Stentoft (2020) emphasized that nowadays critical thinking is at the top of the agenda (Fikriyatii et al, 2022;Maison et al, 2022) and very important and increasingly needed (Ristanto et al, 2022;Suparman, 2022). Facione (2011) confirms that critical thinking skill of our thinking is vital to our quality of life.…”
Section: Introductionmentioning
confidence: 89%
“…These changes in ecosystems lead to the emergence and spread of infectious diseases World Wildlife Fund for Nature (WWF) (2020). Critical thinking skills of students need to be developed in order to create solutions while struggling with environmental challenges and to test whether the solution is indeed an appropriate one (Lesest & Wolbers, 2020;Ristanto et al, 2022). One of the aims of science education is to develop sustainable development awareness, positive attitudes, and behaviors towards the environment and to create solutions to the challenges encountered in humanenvironment interaction (Ministry of Education [MoNE], 2018b;Mongar, 2022).…”
Section: Problem Statusmentioning
confidence: 99%